Eleanor Roosevelt's Radio Broadcasts in France - Luscombe, Anya (European Association for American Studies, 2017)
Eleanor Roosevelt wrote books, thousands of newspaper and magazine articles and was a regular broadcaster. Among the radio programs she hosted, and appeared on, were several for the Voice of America. While she was a US delegate to the United Nations in Paris in 1951 and 1952, Mrs. Roosevelt broadcast a series of weekly radio commentaries aimed at explaining to families in France and other French-speaking countries the workings of the UN and to urge Europeans to work together for peace. These weekly talks generated (as did all Mrs. Roosevelt’s broadcasts) a great deal of letters from the public: usually either extremely favorable or vehemently opposed to the views she expressed. The former First Lady saw the role of the VOA as fundamental to “spread[ing] the understanding of the value of our way of life and of our type of government.” This paper explores the connection between Eleanor Roosevelt and the official US radio propaganda in Europe in the early Fifties and the extent to which American cultural diplomacy benefitted from her presence on the airwaves.
Keywords: radio; Eleanor Roosevelt; Cold War; Communication; History; Political Science and International Relations